Studi Kritis terhadap Dinamika Pendidikan Islam di Andalusia serta Pengaruhnya terhadap Pendidikan Islam - Lidia Putri; Salmi Wati (Jurnal Cakrawala Akademika, 2024)
Abstract. This research describes Andalusia as part of the history of Islamic civilization and also shows that the part of Islam in the west was the golden peak in Islamic history. The research method used in this journal is literature review. The method used involves in-depth analysis of relevant literature sources. Data Analysis Techniques with Content Analysis. The results of this research were that the Andalusian Umayyad Daulah stated that the Islamic government in Andalusia was a turning point for Islamic civilization, along with the fall of Baghdad in the East. Apart from that, this portrait of education can also color various aspects of the life of the surrounding community, especially its influence in the political, social, artistic, cultural and cultural systems which then form a well-organized Islamic education system so that it can make a major contribution to the lives and livelihoods of Muslims towards scientific development. and their intellectuality from time to time.